Characterization of transgene expression in adenoviral vector-based HIV-1 vaccine candidates - Rolling Judith A; Takahashi Marie-Noëlle; Owen Katherine E (Virology Journal, 2010)
Abstract Recombinant adenovirus vectors have been extensively used in gene therapy clinical studies. More recently, the capability of inducing potent cell-mediated and humoral immunity has made these vectors equally attractive candidates for prophylactic or therapeutic vaccine applications. Merck and Co., Inc., developed HIV-1 vaccine candidates based on adenovirus serotype 5 (Ad5) vectors in which the E1 gene, a critical component for adenovirus replication, was replaced by the cytomegalovirus immediate/early promoter, followed by mutated versions of the HIV-1 gag, pol or nef genes (constructs referred to as MRKAd5gag, MRKAd5pol and MRKAd5nef, respectively). Vaccine performance was evaluated in vitro in a novel assay that measures the level of transgene expression in non-permissive A549 cells. Various combinations of vectors were studied. The results indicate that the vaccine induces a dose-dependent expression of the HIV-1 transgenes in vitro. Furthermore, the gag, pol, and nef transgenes are expressed differentially in A549 cells in an MOI-dependent and formulation-dependent manner, yielding an unexpected enhancement of protein expression in trivalent vs. monovalent formulations. Our data suggest that the presence of additional virus in multivalent formulations increases individual transgene expression in A549 cells, even when the amount of DNA encoding the gene of interest remains constant. This enhancement appears to be controlled at the transcriptional level and related to both the total amount of virus and the combination of transgenes present in the formulation.